Facile synthesis and application of aluminum oxide nanoparticle based biodegradable film. Issue 8 (24th May 2021) - Kumar, Harish; Gehlaut, Avneesh Kumar; Gupta, Himanshu; Gaur, Ankur; Kamsonlian, Suantak; Kumar, Devender
Abstract: This study focuses on the synthesis of aluminum oxide nanoparticles (AlO‐NPs) hydrogel through in situ method and formation of biopolymer nanocomposite film. UV–Vis spectroscopy, Fourier transform infrared spectroscopy, scanning electron microscopy, transmission electron microscopy (TEM), particle size analyzer, and energy dispersive X‐ray spectrum were performed for the characterization of AlO‐NPs. TEM micrograph demonstrates the presence of AlO‐NPs in the range of 50–100 nm in the hydrogel network made from sugarcane bagasse carboxymethyl cellulose (SB‐CMC) and synthetic carboxymethyl cellulose (CMC). The successful absorptions peak at 210 nm while conducting UV–Vis spectroscopy suggests existence of AlO‐NPs. The antibacterial properties of AlO‐NPs were analyzed using the disc plate diffusion technique against Gram‐negative bacteria: Escherichia coli (ATCC 433); and Gram‐positive bacteria: Bacillus subtilis (ATCC 1688). AlO‐NPs present in CMCs films reduce moisture content, solubility; elongation at break and increases films' tensile strength. Abstract : This study provides extremely innovative idea to add nanoparticles to biodegradable film, which improves the mechanical properties of film, and thus making it more market friendly.